2020
DOI: 10.3889/oamjms.2020.3989
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subchronic Toxicity Study of the Ethanol Extracts from Ficus deltoidea Leaves in Male Mice

Abstract: BACKGROUND: Ficus deltoidea Jack. leaves have a great potential as traditional medicine, but the safety level of its use is still unknown. AIM: This study aimed to determine the phytochemical contents of the ethanol extract of F. deltoidea leaves and evaluate the level of safety and toxicity through acute and subchronic toxicity tests in mice (Mus musculus). METHODS: The ethanol extract of F. deltoidea leaves was determined for phytochemical contents such as alkaloids, phenolics, flavonoids, coumar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“… 2013 ) and 2000 mg/kg body weight (Nugroho et al. 2020 ), respectively. These observations suggest that F. deltoidea extract can be considered safe and non-toxic for therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“… 2013 ) and 2000 mg/kg body weight (Nugroho et al. 2020 ), respectively. These observations suggest that F. deltoidea extract can be considered safe and non-toxic for therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…Acute and subchronic administration of F. deltoidea extract to male mice did not show clinical signs of toxicity [9]. Subchronic effects of the administration of ethanolic extract of F. deltoidea leaves for 28 days on body weight, absolute organ weight (g), and relative organ weight (%) to body weight of male mice are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Although F. deltoidea has displayed various pharmacological properties, safety information on this plant is still limited. Acute and subchronic toxicity studies of the ethanolic extract of F. deltoidea leaves showed no signs of toxicity in male mice (Mus musculus) after oral treatment with a single 2000 mg/kg body weight dose, while in the subchronic toxicity test, there were no behavioral change and no significant changes in body weight or in the hematological and biochemical parameters of serum [9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is also served as a health tonic or taken as herbal tea to relieve headache, fever, and toothache [29]. Acute toxicity studies showed that the median lethal dose (LD50) of aqueous and ethanolic leaf extracts of F. deltoidea was greater than 5000 mg/kg bwt [30] and 2000 mg/kg bwt [31], respectively. Meanwhile, Abrahim et al [32] showed that F. deltoidea leaves did not exhibit any cytotoxic effects on the normal liver cells.…”
Section: Introductionmentioning
confidence: 99%